Validation of competencies and credentials of venezuelan migrants in Peru - Ricapa Toledo, Moises Bresners O’brian (Espacio Abierto, 2024)
The objective of this study was to analyze the perception of Venezuelan migrant professionals in the processes of validation of competencies and credentials in the Peruvian labour market, 2023. Quantitative, non-experimental and exploratory research with the participation of 163 Venezuelan migrant professionals residing in the Constitutional Province of Callao and Lima, Peru, 2023. The instrument is a questionnaire adapted from the guidelines of the International Organization for Migration (IOM) network. The results show that, by statistically unifying the measurements using multivariate confirmatory techniques, the tetra-factorial configuration of the perceptions examined, corresponding to the proposed theoretical domains of Barriers/Supports, Validation Process, Equity/Discrimination and Socio-labour Integration, it was found that the contrast between barriers and equity deficits was perceived in multiple areas, with some sources of support and limited labour opportunities. Important gaps and obstacles were identified in the processes of validation of academic credentials and previous experience, transversalised by the perceived levels in the dimensions of equity/non-discrimination in comparison with the local population; as well as in the effective possibilities of economic entrepreneurship after migration. While participants recognise intermediate values of social and state support, structural limitations in other critical domains generate a moderate negative to strong critical view on the overall integrative experience after their migratory movement from Venezuela